2018
DOI: 10.1021/jacs.8b09002
|View full text |Cite
|
Sign up to set email alerts
|

Structural Fingerprinting of Protein Aggregates by Dynamic Nuclear Polarization-Enhanced Solid-State NMR at Natural Isotopic Abundance

Abstract: A pathological hallmark of Huntington’s disease (HD) is the formation of neuronal protein deposits containing mutant huntingtin fragments with expanded polyglutamine (polyQ) domains. Prior studies have shown the strengths of solid-state NMR (ssNMR) to probe the atomic structure of such aggregates, but have required in vitro isotopic labeling. Herein, we present an approach for the structural fingerprinting of fibrils through ssNMR at natural isotopic abundance (NA). These methods will enable the spectroscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…81 A recent ssNMR study that employed dynamic nuclear polarization (DNP) allowed for the structural fingerprinting of unlabeled HttEx1 aggregates and provided further evidence for their antiparallel β-sheet assembly. 56,82 In such an antiparallel arrangement, the two ssNMR-revealed β-strand types appear capable of inter-strand hydrogen bonding to each other (but not themselves). An assembled antiparallel β-sheet requires the presence of equal amounts of the two complementary β-strand geometries.…”
Section: Nmr Studies Of Fibrillar Httex1mentioning
confidence: 99%
“…81 A recent ssNMR study that employed dynamic nuclear polarization (DNP) allowed for the structural fingerprinting of unlabeled HttEx1 aggregates and provided further evidence for their antiparallel β-sheet assembly. 56,82 In such an antiparallel arrangement, the two ssNMR-revealed β-strand types appear capable of inter-strand hydrogen bonding to each other (but not themselves). An assembled antiparallel β-sheet requires the presence of equal amounts of the two complementary β-strand geometries.…”
Section: Nmr Studies Of Fibrillar Httex1mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] These results have been obtained thanks to the development of hardware, [17][18][19][20][21][22][23][24][25] polarizing agents, [26][27][28][29][30][31][32][33] and theory. [34][35][36][37][38][39][40][41] Among these developments, the study of samples at natural isotopic abundance thrived, [42][43][44][45][46] especially as a result of efficient methodologies for sample preparation. Indeed, Rossini et al have demonstrated that powders can be impregnated with a radical-containing solution, 47 where the polarizing agent (PA) remains at the surface of the powder particles and the DNP-enhanced 1 H polarization is transferred to the core ...…”
Section: Introductionmentioning
confidence: 99%
“…The assembly kinetics, however, also depends on the polyQ-flanking regions [ 18 , 19 , 20 , 21 , 22 , 23 ]. The in vitro-assembled HTT amyloid is proposed to adopt an antiparallel β-sheet arrangement [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Yet, despite intense efforts, the atomic resolution 3D architecture of aggregated HTT , even assembled in the test tube, remains elusive.…”
mentioning
confidence: 99%
“…The tight interdigitation of glutamine sidechains in the packing of antiparallel β-sheets in HTTQex1 requires these sidechains to adopt two different rotamers for different strands [ 43 ], indicating structural heterogeneity at single-residue level. Specifically, the Qs of the two β-strands in the HTTQex1 β-hairpin differ in their side chain dihedral angles; however, within each strand, all Q residues are the same rotamers with the same backbone and sidechain geometry [ 28 , 43 ]. In this antiparallel arrangement, inter-strand hydrogen bonds are only formed between β-strands with different sidechain rotamers, but not between β-strands with the same rotamer [ 28 , 43 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation